Determination of Fuel Type for Optimal Performance and Emission in a CI Engine Used Biodiesel and its Blends via Multi-Criteria Decision Making - SAYIN, CENK (My University, 2019)
In this study, fuel type which provides optimum performance and emission in compression ignition (CI)engine used alternative fuel was determined by COPRAS (Complex Proportional Assessment) in multicriteriadecision making (MCDM), and it was ranked from good to bad. Furthermore, the engineperformance and emission consequences obtained from the use of fuels are discussed. In the experiments,pure biodiesel, diesel, and biodiesel/diesel blend fuels at a ratio of 5, 20 and 50% by volume were used asan alternative fuel. The performance and exhaust emission characteristics of the engine have been obtainedin the tests performed at 7.2 kW power output and 1500 rpm of the constant engine speed. According toexperimental results, with the uptrend of the biodiesel ratio in the blended fuel, it has been observed thatwhile the specific fuel consumption (SFC) is enhanced to diesel, the thermal efficiency (η) is partiallyreduced. At the same time, the emissions of the nitrogen oxide (NOx), carbon monoxide (CO) hydrocarbon(HC), and carbon monoxide (CO) decreased while the carbon dioxide (CO2) emission enhanced. Accordingto the COPRAS method, the ranking of fuels from best to worst was calculated as B5>B20>B50>B0>B100.
Keywords: Biyoloji Çeşitliliğinin Korunması; Biyoloji; Kimya, Analitik; Kimya, Uygulamalı; Kimya, İnorganik ve Nükleer; Kimya, Tıbbi; Kimya, Organik; Fizikokimya; Ekoloji; Entomoloji; Çevre Bilimleri; Genetik ve Kalıtım; Matematik; Optik; Kuş Bilimi; Paleontoloji; Parazitoloji; Fizik, Uygulamalı; Fizik, Atomik ve Moleküler Kimya; Fizik, Katı Hal; Fizik, Akışkanlar ve Plazma; Fizik, Matematik; Fizik, Nükleer; Fizik, Partiküller ve Alanlar; Spektroskopi; İstatistik ve Olasılık; Termodinamik; Taşınım; Su Kaynakları; Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Sibernitik; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; İnşaat ve Yapı Teknolojisi; Savunma Bilimleri; Enerji ve Yakıtlar; Mühendislik, Kimya; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Çevre Mühendisliği; Mühendislik, Jeoloji; Endüstri Mühendisliği; İmalat Mühendisliği; Mühendislik, Makine; Gıda Bilimi ve Teknolojisi; Jeoloji; Yeşil, Sürdürülebilir Bilim ve Teknoloji; Görüntüleme Bilimi ve Fotoğraf Teknolojisi; Denizcilik; Metalürji Mühendisliği; Nanobilim ve Nanoteknoloji; Robotik; Telekomünikasyon